Understanding the archaeological record - Lucas, Gavin 1965- (Cambridge Cambridge University Press, 2012)
"This book explores the diverse understandings of the archaeological record in both historical and contemporary perspective, while also serving as a guide to reassessing current views. Gavin Lucas argues that archaeological theory has become both too fragmented and disconnected from the particular nature of archaeological evidence. The book examines three ways of understanding the archaeological record - as historical sources, through formation theory, and as material culture - then reveals ways to connect these three domains through a reconsideration of archaeological entities and archaeological practice. Ultimately, Lucas calls for a rethinking of the nature of the archaeological record and the kind of history and narratives written from it"-- Provided by publisher
Machine generated contents note: 1. The trouble with theory; 2. The total record; 3. Formation theory; 4. Materialized culture; 5. Archaeological entities; 6. Archaeological interventions; 7. A 'new' social archaeology?
Title from title screen (viewed October 27, 2023)
Electronic reproduction
Keywords: Archaeology -- Philosophy; Archaeology -- Methodology; History -- Sources; Ontology; Antiquities; Material culture; Social archaeology